National market of reference materials. Curreent state, problems, and development prospects. Part 1. Introduction. Development of the national market of reference materials - Yu. S. Bessonov; O. N. Kremleva (Стандартные образцы)
The present publication begins a cycle of papers of specialists from the Scientific Methodical Centre at the State Service of Reference Materials for Composition and Properties of Substances and Materials. These papers will be devoted to the problematic issues of forming and developing the national market of reference materials in terms of requirements imposed by the current legislation of the Russian Federation concerning of measurement uniformity assurance, technical regulation and accreditation in the national accreditation system.Publications are aimed at giving the reader an insight into the common practice of development and use of reference materials of various categories, state regulation procedures when producing and using reference materials taking into account modern requirements in the field of metrological assurance and measurement uniformity in Russia and abroad, together with necessity and importance of harmonization in the field of reference materials, as well as some other aspects of this activity.This paper discusses main aspects concerning the state of the reference materials market in the Russian Federation and suggestions on its development taking into account modern requirements. The role of state regulation when creating the national market of reference materials in the Russian Federation is shown. The paper specifies possible directions for reference materials production, meeting modern metrological requirements imposed on measurements in the sphere of the state regulation of measurement uniformity assurance.